Adipocyte-Specific Fatty Acid-Binding Protein (AFABP) and Chemerin in Association with Gestational Diabetes: A Case-Control Study - Maryam Mosavat; Mitra Mirsanjari; Bashir A. Lwaleed; Maherah Kamarudin; Siti Zawiah Omar (Journal of Diabetes Research)
Background. Adipocytokines participate in regulating the inflammatory response in glucose homeostasis and type 2 diabetes. However, among these peptides, the role of adipocyte-specific fatty-acid-binding protein (AFABP), chemerin, and secreted protein acidic and rich in cysteine (SPARC) in gestational diabetes (GDM) has not been fully investigated. Method. The maternal fasting level of adipocytokines of 53 subjects with GDM and 43 normal pregnant (NGDM) was measured using multiplex immunoassay at 24–28 weeks, before delivery, immediate postpartum, and 2–6 months postpuerperium. Results. Higher levels of AFABP were associated with a 3.7-fold higher risk of GDM. Low chemerin levels were associated with a 3.6-fold higher risk of GDM. Interleukin-10 (IL-10) was inversely associated with the risk of GDM. SPARC had no association with GDM. AFABP was directly correlated to interleukin-6 (r=0.50), insulin resistance index (r=0.26), and body mass index (r=0.28) and inversely correlated to C-reactive protein (r=−0.27). Chemerin levels were directly and strongly correlated with IL-10 (r=0.41) and interleukin-4 (r=0.50) and inversely correlated to insulin resistance index (r=−0.23) in GDM but not NGDM. In the longitudinal assessment, there were no significant differences in AFABP and chemerin concentrations of both studied groups. Conclusion. AFABP and chemerin were associated with a higher risk of GDM. These adipocytokines were related to insulin resistance, body mass index, and inflammation in pregnant women diagnosed with GDM.